Characterization and Antimicrobial Characteristics of Chitosan Modified Hibiscus Sabdariffal.Extract - Mansour, Fatma Elzhraa (JOURNAL OF ADVANCES IN PHYSICS, 2018)
Samples of Chitosan (Cs) natural polymer containing successive amount of Hibiscus sabdariffaLextract were sucssesfuly synthesized using traditional simple casting route. Prepared thin films were characterized using fourier transform infrared (FTIR). FT-IR of synthesized thin films reveals maintenance of the characteristic bands of chitosan in addition to the appearance of two new sharp intense bands at 1782 and 954 cm-1 intensified with increasing plant extract content and assigned to the interaction between NH2 of polymer skeleton with falvanoids present in the extract. Obtained data poit out to a formation of homogenous composite structure. X-ray diffraction data (XRD) reval no prounounced band indicating the amorphous structure of synthesized final polymeric product. In vitro antimicrobial studies were performed using both gram negative and positive bacteria in addition to Fungul and Yeast activity using simple minimum inhibition zone (MIZ) standeredroutain.